Metacercariae of Tylodelphys sp. (Trematoda: Diplostomidae) parasite of Brochis multiradiatus and Corydoras splendens (Siluriformes: Callichthyidae) from the Peruvian Amazon - Germán Augusto Murrieta Morey (Acta Scientiarum. Biological Sciences, 2018)
Corydoras splendens (Castelnau, 1855) and Brochis multiradiatus (Orcés V., 1960) are highly demanded for exporters in the Peruvian Amazon and importers all over the world.  The exportation of this fish species may represent a gateway for endoparasites to enter in a new environment with serious effects, so, the present study reports the presence of Tylodelphys sp. infecting C. splendens and B. multiradiatus. Fish were acquired from fishermen of the city of Iquitos, Peru. After the necropsy and analyses of the fish, metacercariae of Tylodelphys sp. were found in the liver and intestine. This finding represents the first report of Tylodelphys Diesing, 1850 infecting a fish in the Peruvian Amazon. Considering the possible damages caused by species of Tylodelphys, highlighting the nutritional and respiratory ones, prophylactic measures must be taken into consideration for exporters to avoid some damages in the fish that can deteriorate their health and also to avoid the introduction of this parasite to other countries.